Macroeconomic essence of Takaful: exploring the significance and impact of Takaful in macroeconomic context / Irfan Shahid. - Shahid, Irfan (Universiti Teknologi MARA Selangor, 2018)
Takaful is an Islamic concept of modern insurance. It is based on cooperation and mutual understanding. Takaful has a significant position in the financial market. Conventional insurance has also opened the window for takaful in the Middle East and African countries. Takaful is considered one of the lucrative industries in the financial market. Several aspects of Takaful were explained in various books and monographs. There are numerous benefits of Takaful studied in various research, but takaful has some significant aspects in Macroeconomics literature. It helps to grow the economy by enhancing the productivity and economic security. The paper aims to analyse theoretically the impact of Islamic insurance on production, consumption and investment to study the impact of Takaful on Gross Domestic Product of Economy.